2015
DOI: 10.1016/j.ebiom.2015.10.028
|View full text |Cite
|
Sign up to set email alerts
|

A novel genomic alteration of LSAMP associates with aggressive prostate cancer in African American men

Abstract: Evaluation of cancer genomes in global context is of great interest in light of changing ethnic distribution of the world population. We focused our study on men of African ancestry because of their disproportionately higher rate of prostate cancer (CaP) incidence and mortality. We present a systematic whole genome analyses, revealing alterations that differentiate African American (AA) and Caucasian American (CA) CaP genomes. We discovered a recurrent deletion on chromosome 3q13.31 centering on the LSAMP locu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 57 publications
3
57
0
Order By: Relevance
“…Its protein product is also expressed in colon and platelets. Interestingly, LSAMP somatic deletions were associated with prostate cancer specifically in AAs 25 . The top ranked variant, rs72947885, is located in the 3’UTR and also overlaps with several transcriptional regulator motifs and is also reported by Ensembl to be in an enhancer region (ENSR00001988698) in some cell lines including B cells and M1 macrophages from venous blood.…”
Section: Discussionmentioning
confidence: 99%
“…Its protein product is also expressed in colon and platelets. Interestingly, LSAMP somatic deletions were associated with prostate cancer specifically in AAs 25 . The top ranked variant, rs72947885, is located in the 3’UTR and also overlaps with several transcriptional regulator motifs and is also reported by Ensembl to be in an enhancer region (ENSR00001988698) in some cell lines including B cells and M1 macrophages from venous blood.…”
Section: Discussionmentioning
confidence: 99%
“…This shared genetic background may confer similarities in cancer incidence and outcomes in populations. Recent large-scale genomic profile studies in individual cancer types, such as prostate (Huang et al, 2017; Petrovics et al, 2015; Powell et al, 2013; Wang et al, 2017), breast (Ademuyiwa et al, 2017; Huo et al, 2017; Keenan et al, 2015; Loo et al, 2011), colon (Guda et al, 2015), lung (Araujo et al, 2015; Campbell et al, 2017; Kytola et al, 2017), gastric (Schumacher et al, 2017), esophageal (Deng et al, 2017), and kidney (Krishnan et al, 2016) cancers have robustly demonstrated that genomic differences in cancers exist among distinct racial and ethnic populations. Consistently, it has been reported that the genetic background of patients may influence specific somatic alterations in cancer genomes during tumorigenesis (Carter et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using AIMs have revealed the susceptibility of PCa association analyses to such confounding influence, and the need to take into account substructure caused by differences in relative ancestral genetic contributions between cases and controls (Erdei et al, 2011;Ricks-Santi et al, 2012;Petrovics et al, 2015). Prior investigations have explored the relationship between "skin color" and genomic ancestry estimated by AIMs Reddy et al, 2003;Pimenta et al, 2006;Suarez-Kurtz et al, 2007;Whitman et al, 2010;Lins et al, 2011;Ricks-Santi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%